Socio-professional communities as a subject of sociological analysis - D. V. Ulyanov (Цифровая социология, 2024)
The article provides an in-depth research of socio-professional communities as a subject of sociological analysis. They play an increasingly important role in civil society, being flexible and diverse in terms of socio-professional orientation. Their development is closely connected with the expansion of communicative ties between different interest associations. The communities unite representatives of various professions and types of labour and are independent public organisations, the diversity of which is conditioned by the dynamics of the forming market of professions and the demands of the developing economy. The relevance of the research is determined by the need to study socio-professional communities as an important element of civil society. The article analyses in detail their main characteristics, role in the formation of civil society and development prospects. Various aspects of socio-professional communities are considered, including the structure, functions. Particular attention is paid to analysing their interaction with other elements of civil society such as political parties, public organisations and mass media. This study is important for understanding the role of socio-professional communities in contemporary society and can serve as a basis to develop effective strategies and policies in the area.